2014
DOI: 10.1002/anie.201408151
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Imidazolium Salt Intimate (Contact) Ion Pairs in Solution

Abstract: 1-n-Butyl-2,3-dimethylimidazolium (BMMI) ionic liquids (ILs) associated with different anions undergo H/D exchange preferentially at 2-Me group of the imidazolium in deuterated solvents. This process is mainly related to the existence of ion pairs rather than the anion basicity. The H/D exchange occurs in solvents (CDCl3 and MeCN for instance) in which intimate contact ion pairs are present and the anion possesses a labile H in its structure, such as hydrogen carbonate and prolinate. In D2 O, separated ion pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
5
41
0
Order By: Relevance
“…Using ion pairs of ILs containing the BMMI cation and anions such as chloride, prolinate, formiate, and bicarbonate, stable contact ion pairs have been maintained in chloroform, transient ion pairs in DMSO, and instantaneous ion pair dissociation has been observed in water. [74] These findings are in agreement with the experimentally detected tendency of lower association constants for ion pair formation in more polar solvents.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 88%
See 2 more Smart Citations
“…Using ion pairs of ILs containing the BMMI cation and anions such as chloride, prolinate, formiate, and bicarbonate, stable contact ion pairs have been maintained in chloroform, transient ion pairs in DMSO, and instantaneous ion pair dissociation has been observed in water. [74] These findings are in agreement with the experimentally detected tendency of lower association constants for ion pair formation in more polar solvents.…”
Section: Molecular Dynamics Simulationssupporting
confidence: 88%
“…[71,72] This behaviour remains if small amounts of water are added which then compete with the CO 2 for the favourite interaction sites. [73] 1 H, 13 C-HOESY experiments also revealed that contact ion pairs are maintained for BMI·HCO 3 [74] Moreover, these species display reactivity as contact ion pairs and not as solvent-separated ions when diluted in CDCl 3 , CD 3 CN and even in DMSO, but not in D 2 O (see below).…”
Section: Long-lived Contact Ion Pairs Detected By Nmr Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the oxidized palladium component increases with the decrease of the ionic bond strength between the imidazolium cation and anions, i.e., the stronger the ionic interaction between the cation and anion, the less "ionic" is the contact ion pair. Hence, the interaction of the IL with the metal surface is via IL contact pairs (or aggregates) 54,55 rather than by charged species, corroborating the proposed supramolecular model for formation and stabilization of M-NPs in ILs. [56][57][58] …”
Section: Chemical State and Local Atomic Order Of The Pd Atomssupporting
confidence: 74%
“…[3][4][5] One of the most singularp roperties of ionicl iquids( ILs)resultingf rom their supramolecular structuralo rganization-is the presence of nonhomogeneousn anodomains that can easily accommodate both polar and nonpolar compounds. Consequently,c ooperative networks (based on dispersive forces andh ydrogen bonds)o fc lassical imidazolium ILs such as BMIm·BF 4 and BMIm·PF 6 are only marginally disrupted and the cation-anionc ontact ion pair [13,14] is unaffected by the inclusion of CO 2 . [4,7,8] This is mainly owed to the high CO 2 solubility in ILs as well as the possibility to fine-tune the sorption properties of the ionic material.…”
Section: Introductionmentioning
confidence: 99%